Transformation of values of ironic at transition from modern to postmodern - T. A. Medvedeva (Известия Томского политехнического университета: Инжиниринг георесурсов, 2019)
The historical and philosophical approach traditional for researching irony closes this phenomenon within a particular philosophical system and does not allow answering the question about its genesis and mechanism of sociocultural functioning. The dialogical logic combining proper philosophical and cultural approaches was selected as a methodology to extend the field of analysis. On the basis of its theoretical and methodological principles it becomes possible to state the basic research problem - to identify the conjugation of anthropological and sociocultural irony in the mechanism of its functioning by the example of the period of European cultural paradigm change. As a result, the author determined the causes and patterns of irony values transformation in situation of transition from modern to postmodern and disclosed the characteristics of modernistic and postmodernistic irony as the substantial feature of cultural awareness and artistic technique, found a link of postmodern interpretation of irony concept to the formation of postmetaphysical type of philosophical thinking, stated the characteristic irony as vital strategy in a crisis of values. Thus, the implementation of the chosen methodology allowed the author to examine the phenomenon of irony from the perspectives of anthropologically oriented philosophy of culture.